2006
DOI: 10.1159/000094158
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers after Traumatic and Hypoxemic Brain Injuries: Insight into the Biochemical Response of the Pediatric Brain to Inflicted Brain Injury

Abstract: Inflicted traumatic brain injury (iTBI) involves a combination of mechanical trauma and hypoxemia. Serum biomarker concentrations may provide objective information about their relative importance to the pathophysiology of iTBI. We compared the time course of neuron-specific enolase (NSE), S100B and myelin basic protein after pediatric hypoxic-ischemic brain injury, iTBI and noninflicted TBI (nTBI). The time to reach peak concentrations of all three biomarkers was shorter after nTBI. Initial and peak S100B, ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(41 citation statements)
references
References 86 publications
3
37
1
Order By: Relevance
“…In contrast to previous studies by our group which have suggested that differences in age and/or injury mechanism are associated with different biomarker levels [12,37], in the current study, neither age nor mechanism was associated with the different trajectories, suggesting that the group differences are due to other factors. Given the small sample sizes for the non-low-decliner groups, it is difficult to determine the etiology of these differences, though one might hypothesize that the high-risk trajectories are related in some way to the type of cell death (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies by our group which have suggested that differences in age and/or injury mechanism are associated with different biomarker levels [12,37], in the current study, neither age nor mechanism was associated with the different trajectories, suggesting that the group differences are due to other factors. Given the small sample sizes for the non-low-decliner groups, it is difficult to determine the etiology of these differences, though one might hypothesize that the high-risk trajectories are related in some way to the type of cell death (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…We measured NSE and S100B in all serial samples until there were 2 consecutive normal values. Data from hundreds of subjects over the past 10 years suggest that once NSE and S100B values decrease to within the normal range, a subsequent increase to the abnormal range would be very uncommon [12,13,37]. Because MBP does not increase until approximately 48 h after injury, we measured serial concentrations of MBP in all subjects until 60 h after injury; subjects who had a normal MBP concentration at that time point did not have additional MBP concentrations measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports suggested that biomarkers might be valuable in pediatric TBI [2,5,12,13,14,15,16,17,18,19,20]. The most highly cited article from the supplement, by Dr. Rachel Berger et al [2], serially assessed three serum biomarkers [neuron-specific enolase (NSE), S100B and myelin basic protein (MBP)] across three diseases in the pediatric intensive care unit (PICU), namely TBI, abusive head trauma and cardiopulmonary arrest. The report indicated that the biomarker profiles across these three diseases appear to be different, both with regard to timing and marker composition.…”
Section: Biomarkersmentioning
confidence: 99%
“…The field was ready for such a supplement, and its timing coincided with a period of considerable growth both in this area of research and in the emerging subspecialty of pediatric neurocritical care. Several of the reports in that issue have become well-cited works, and it is likely not a coincidence that the most highly cited articles addressed some of the hot-button areas of investigation in TBI [1,2,3,4,5]. This review is part of a new second supplement on this topic published in Developmental Neuroscience.…”
Section: Introductionmentioning
confidence: 99%